Some polychaetous annelids from Hong Kong waters - Shin, Paul K. S. ([Edited book chapter. Workshop proceedings], 1982)
Some polychaetous annelids collected from Hong Kong waters, particularly in Tolo Harbour and Tolo Channel, have been studied. A total of forty-eight species have been recorded and of these, thirty-eight species are reported upon for the first time in Hong Kong. The zoogeographical affinities of these species are briefly analysed. It is shown, from the present results, that the polychaete fauna of Hong Kong belongs to the tropical Indo-Malayan subregion of the Indo-west-Pacific province.
Annelidabase. Not known to be online except here at WoRMS